Privacy Protection for HealthGrid Applications - Claerhout, B.; De Moor, G. J. E. (Methods of Information in Medicine, 2005)
Objectives: This contribution aims at introducing the problem of privacy protection in e-Health and at describing a number of existing privacy enhancing techniques (PETs). The recognition that privacy constitutes a fundamental right is gradually entering public awareness. Because healthcare-related data are susceptible to being abused for many obvious reasons, public apprehension about privacy has focused on medical data. Public authorities have become convinced of the need to enforce privacy protection and make considerable efforts for promoting through privacy protection legislation the deployment of PETs.Methods: Based on the study of the specific features of Grid technology, ways in which PET services could be integrated in the HealthGrid are being analyzed. Grid technology aims at removing barriers between local and remote resources. The privacy and legal issues raised by the HealthGrid are caused by the transparent interchange and processing of sensitive medical information. PET technology has already proven its usefulness for privacy protection in health-related marketing and research data collection.Results: While this paper does not describe market-ready solutions for privacy protection in the HealthGrid, it puts forward several cases in which the Grid may benefit from PETs.Conclusion: Early integration of privacy protection services into the HealthGrid can lead to a synergy that is beneficial for the development of the HealthGrid itself.
Keywords: Privacy; privacy enhancing techniques (PETs); HealthGrid; Grid